Median Versus Paramedian Spinal Anesthesia: PDPH Incidence in Urological Procedures. - Alarfi, Aosama; Saleh, Adel; Zayd, Wisam; Elmansori, Abdelhaq (Scientific Journal of University of Benghazi, 2025)
Spinal anaesthesia is a popular method for anaesthesia in the lower body, offering advantages over general anaesthesia. The paramedian and median methods are most commonly used. Spinal anaesthesia has many benefits, but postdural puncture headache (PDPH) is the most common risk. This study aimed to find out how often PDPH happens in Libyan patients having spinal anaesthesia for urological surgeries, comparing the median and paramedian methods because there are not many records available. This prospective study occurred at the Specialty Surgical Centre in Benghazi, Libya, from September 18, 2019, to February 18, 2020. Patients undergoing urological surgery under spinal anaesthesia were divided into two groups based on the method used: median (Group M) and paramedian (Group P). Researchers collected age, BMI, and gender data to better understand PDPH prevalence and compare the two companies. All the data were coded and analysed using SPSS 27. The study included 60 patients, including 53 adult males and 7 females, ranging in age from 11 to 70 years, with a median age of 55.5 ± 18.2 years. Normal PDPH prevalence was 8.3%, with 13.3% in Group M and 3.3% in Group P. Statistical analysis showed no significant difference in PDPH prevalence between the two companies (p=0.4). Patients’ age, gender, and BMI did not differ significantly between the two groups, according to logistic regression analysis. While a larger number of patients in the median institution had PDPH, the difference was not statistically significant. These findings support previous research on needle insertion techniques and PDPH, but the authors suggest conducting larger studies with more populations to confirm and improve those findings.